Hans Jonas: the early years - Herskowitz, Daniel M.; Lapidot, Elʿad; Wiese, Christian (Routledge Jewish studies series, 2025)
"This book offers new perspectives on the early and formative years of the German-Jewish philosopher Hans Jonas, through innovative studies of his German and Hebrew work in pre-war Germany and Palestine. Covering all facets of Jonas's early work, the book brings together leading scholars to explore key conceptual, historical, genealogical, and biographical contexts. Some of the main topics examined include his deep intellectual history of Western thought and its origins in late antiquity through the category of Gnosis, the intellectual influence of Heidegger, Bultmann, Husserl, and Spengler, his relation to Christian theology, and his interest in Judaism and Zionism. Existing research on his early work is not only limited in size but also often methodologically deficient, for it is common to interpret the early in light of the late and as teleologically leading to it. By introducing new materials and addressing new questions, this book offers innovative perspectives on Jonas's intellectual project as a whole and provides a historical and conceptual foundation for further scholarly explorations of his oeuvre. Providing fresh insights into the work of one of the twentieth century's most influential philosophers, the book will appeal to students and researchers working in intellectual history, Jewish studies, and religion"--